2020
DOI: 10.2174/1871527319666200611130804
|View full text |Cite
|
Sign up to set email alerts
|

When Sick Brain and Hopelessness Meet: Some Aspects of Suicidality in the Neurological Patient

Abstract: : Neurological diseases expose individuals to a higher risk of suicidal ideation and suicidal behavior, including completed suicides and suicide attempts. They also represent a paradigmatic arena to study the etio-pathogenic mechanisms underlying suicidality because they are emblematic of the heterogeneity and complexity of mutual interrelationships characterizing this issue. On the one hand, neurological diseases imply strictly biological impairments that are postulated to be the basis of vulnerability to sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
(69 reference statements)
2
36
0
Order By: Relevance
“…In these two cases, possible AD diagnosis was attributed to both patients as their neuropsychiatric symptoms were well-correlated with progressive neurodegeneration in the brain. The presence of SB in these two cases was also consistent with the increased risk of suicidality in patients with AD [45][46][47][48][49]. However, unlike AD, in both cases the cognitive and psychiatric aggravation was rapid (within 2-3 years) and consistent with previously documented progression of these symptoms in CTE [50].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In these two cases, possible AD diagnosis was attributed to both patients as their neuropsychiatric symptoms were well-correlated with progressive neurodegeneration in the brain. The presence of SB in these two cases was also consistent with the increased risk of suicidality in patients with AD [45][46][47][48][49]. However, unlike AD, in both cases the cognitive and psychiatric aggravation was rapid (within 2-3 years) and consistent with previously documented progression of these symptoms in CTE [50].…”
Section: Discussionsupporting
confidence: 85%
“…Collectively, these findings suggest the possible existence of a neurobiological pathway that is affected in both CTE and dementia [75,76]. Since dementia has been associated with increased suicide risk [45,46,77], it is likely that suicidality might be the ultimate consequence of this common neuropathology in CTE and dementia. Specifically, these patients may experience pronounced social stigma for this inevitable degeneration in cognitive status, eventually increasing their risk for SI and SB.…”
Section: Neurobiological Hypotheses For the Development Of Suicidalitmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous papers have suggested that the symptom of CTE present as a form of dementia with characteristics approachable to front-temporal dementia in the later age of retired athletes [ 33 ], even in athletes of younger age, the mental health-related behavioural symptoms including depression alongside cognitive impairment and anger control problems may commence insidiously as CTE signs [ 34 ]. In addition, other research has pointed out that CTE, mood disorder, and suicidality have mutual and complex associations with each other [ 35 , 36 ]. Therefore, the possibility that some symptoms detected by the BDSA-J may suggest CTE and its related symptoms cannot be rigidly excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, neurological diseases, pain, and oncological conditions occurred more frequently in the suicidal elderly. An association between neurologic diseases and SI, SA, and SB was observed (6,12,(51)(52)(53)(54)(55), especially for stroke and hemiplegia (4,11,13,56,57), epilepsy (4,8,45,58), and dementia (13,59,60). A greater rate of SI was documented in patients with Parkinson's disease (60,61), and the role of sub-thalamic deep brain stimulation (DBS) on suicidality risk in patients treated for extrapyramidal movement disorders is still discussed [for a recent systematic review, see (62)].…”
Section: And Some Common Clinical Featuresmentioning
confidence: 99%